Global Board Market Index Shariah: A Comprehensive Analysis of the 2020-2023 Trends - Akbar, Aldi; Kartawinata, Budi Rustandi; Hidayat, Agus Maolana (Journal of Business Management and Economic Development, 2024)
Global stock markets experienced several spikes and dips during the pandemic. In March 2020, there was a sharp decline in many stock exchanges around the world, known as "Black Thursday". Major stock indice such as S&P 1200 Global Board Market Index (BMI) Shariah experienced significant declines in a short period of time. However, since those declines, global stock markets have experienced a strong recovery. Huge economic stimulus, hopes for a COVID-19 vaccine, and measures to ease restrictions have made investors more optimistic. Many major stock indices have managed to reach new highs in recent months. The movement of of the global Islamic stock market during the pandemic also depends on regional and country-specific factors. Overall, the global Islamic stock market experienced volatility during the COVID-19 pandemic, but has shown signs of recovery. Investment decisions in the global Islamic stock market during the pandemic need to take into account factors that affect sector and country-specific performance.